Predictors of hematologic response and survival with stem cell transplantation in AL amyloidosis: A 25‐year longitudinal study. Issue 9 (5th July 2022) - Gustine, Joshua N.; Staron, Andrew; Szalat, Raphael E.; Mendelson, Lisa M.; Joshi, Tracy; Ruberg, Frederick L.; Siddiqi, Omar; Gopal, Deepa M.; Edwards, Camille V.; Havasi, Andrea; Kaku, Michelle; Lau, K. H. Vincent; et al.
Abstract: High‐dose melphalan and stem cell transplantation (HDM/SCT) is an effective treatment for selected patients with AL amyloidosis. We report the long‐term outcomes of 648 patients with AL amyloidosis treated with HDM/SCT over 25 years. Hematologic CR was achieved by 39% of patients. The median duration of hematologic CR was 12.3 years, and 45% of patients with a hematologic CR had no evidence of a recurrent plasma cell dyscrasia at 15 years after HDM/SCT. With a median follow‐up interval of 8 years, the median event‐free survival (EFS) and overall survival (OS) were 3.3 and 7.6 years, respectively. Patients with a hematologic CR had a median OS of 15 years, and 30% of these patients survived >20 years. On multivariable analysis, dFLC >180 mg/L and BM plasma cells >10% were independently associated with shorter EFS, whereas BNP >81 pg/mL, troponin I > 0.1 ng/mL, and serum creatinine >2.0 mg/dL were independently associated with shorter OS. We developed a prognostic score for EFS, which incorporated dFLC >180 mg/L and BMPC% >10% as adverse risk factors. Patients with low‐risk (0 factors), intermediate‐risk (1 factor), and high‐risk (2 factors) disease had median EFS estimates of 5.3, 2.8, and 1.0 years, respectively ( p < .001). The 100‐day treatment‐related mortality rate was 3% in the latest treatment period (2012–2021), and the 25‐year risk of t‐MDS/AML was 3%. We conclude that HDM/SCT induces durable hematologic responses and prolonged survival with improved safety in selected patients with AL amyloidosis. Abstract :